Cardiovascular Ergometry and Telemetry in Biomedical Control of Cuban Athlete - Teresita Duany-Díaz; Cesia Rivera Garmendía; Margiolis Colás Viant (Revista de Investigación e Innovación en Ciencias de la Salud)
Introduction. The digital transformation in health drives the increase of new software, aligned with the dynamics of the development of information and communications technologies (ICTs).